Identifikasi Perilaku Bullying di Tingkat Sekolah Menengah - Supriyanto, Agus; Prasetiawan, Hardi; Wahyudi, Amien (STKIP Muhammadiyah Pringsewu, 2018)
Bullying behavior is harmful to the perpetrator and the victim. The goal of this research to identify the forms of bullying and locations of bullying. Descriptive study with bullying behavior scale instrument on 300 students and analyzed descriptively. The findings that bullying behavior is verbal, physical, relational, and cyber. Verbal bullying behavior through angry, mocking, laughing, cursing, and make friends. Relational bullying through gossip, excommunication, seniority, gangs, and sneers. Bullying is physically by grabbing, hitting, fighting, and charging. Cyberbullying through intimidation, spreading good names, and engineering images. Bullying behavior occurs in schools, at home, and in the neighborhood. The role of school counselors for the prevention and eradication through guidance and counseling programs.Â Keywords:Â bullying, secondary school.